The forgotten local foot soldiers of folk - Mohd Azmyl, Md Yusof * (The Malaysian Insight, 2023)
THE most notable figures in popular music during the 1960s, who used the medium as a powerful platform to disseminate new political ideas, were Bob Dylan and The Beatles.